Socio-economic Conditions in Two Sectors of the ChorotegaBiological Corridor: Community perceptions - Alarcón, Yusselfy (2009)
Socio-economics aspects involved in the conservation of Chorotega Biological Corridor, sectors Diriá-Ostional and Cerros del Rosario were identified in November 2008. We used qualitative and quantitative methodologies for social research to collect information about perception by people and institutions involved in the study area. Design of tools was focused on identify use, management, threat and knowledge about biological corridor from communities involved. Information obtained to suggest that knowledge about biological corridors is poor. Absent of knowledge on environmental issues, sparse development of training programs by institutions related and lack of coordination between these and municipality, limit efforts to conserve natural resources.